Factors causing variation orders of mosque construction in Perak, Malaysia: a case study / Mohd Nazri Abdullah and Syed Haris Syed Mustapa - Abdullah, Mohd Nazri; Syed Mustapa, Syed Haris (2021)
Variation order is a formal document used for any form of amendment during construction on an agreed-upon, well-defined scope or schedule of works. Variations are mostly inevitable despite leading to dispute among stakeholders, affecting labour's productivity and consume time and cost. Variation order was treated variedly according to the conditions of the contract of the particular construction. This study focused on mosque projects as per Public Work Department condition of contract which is Public Work Department Form of Contract PWD203a 2010 with quantity and Public Work Department Form of Contract PWD203 2010 with drawings and specifications. Both of the articles of agreement partake different approaches on variation order calculation specifically on the cost incurred. This paper aims to identify the variation order factors of mosque construction in Perak and identify the contributors that caused variation orders of mosque constructions in Perak, Malaysia.This research employs document analysis and a total of 10 projects have been analysed.